Acoustic Performance of Upcycled Materials: Plastics & Cigarette Buds in Laminate Composites - R Sivakumar, Ganahcan Nair; Zainulabidin, Muhd Hafeez (Research Progress in Mechanical and Manufacturing Engineering, 2024)
This study investigates the capacity of repurposed materials, such as PET powder derived from plastic bottles and cigarette butts, for the purpose of sound absorption. The objective of the research is to create numerical simulation models that can accurately forecast the sound absorption characteristics of laminate composites. It also seeks to investigate the relationship between material qualities and the arrangement of the laminate, and to provide dependable techniques for predicting the sound absorption coefficient. The research seeks to harness the capabilities of these materials for novel noise mitigation methods, thereby enhancing environmental health and acoustic well-being.